Penerapan Model CA-Markov untuk Prediksi Perubahan Penggunaan Lahan Perkotaan Bereuneun, Aceh Tahun 2034 - Muhammad Aldy Umra; Mirza Irwansyah; Farisa Sabila (Universitas Syiah Kuala, 2023)
The increase in economy and population in Aceh Province, which is increasing yearly, affects new development in Aceh, including the Beureunuen Urban Area (KPB). KPB Based on the Qanun RTRW of Pidie Regency in 2014-2034 is intended as a fast-growing and trading area with a district scale whose management direction is on the development of the trade sector, development of the agricultural sector, development of the agricultural product processing industry, and control of space utilization and land function change. The KPB is also focused on a productive economic area for food security through the development of agricultural land. KPB also developed into an urban center serving the eastern, southern, and western areas of Pidie Regency due to its location which is crossed by the east causeway connecting the Banda Aceh-Medan development center and the Meulaboh development center (West Aceh). These things affect the development that occurs in the KPB so the KPB requires control of land use change so that the sustainability of development and the environment is maintained. This study aims to see the land changes that occurred in the KPB in 2004, 2017, 2021, and the predictions for 2034, and their suitability to the Pidie Regency RTRW in 2014-2034. The analysis method used to see changes and predictions of land use using Cellular Automata-Markov (CA-Markov) with the supervised classification method with the Maximum Likelihood Classification (MLC) algorithm was then carried out as an overlay method using QGis. The results show that the KPB has increased built-up land and agricultural land from 2004-2021. The increase has an impact on the decline in vegetation land. The 2034 prediction results illustrate that there is an increase in built-up land and a reduction in agricultural land and vegetation. The overlay results show that the suitability of land use by 78% with the use of built-up land has exceeded the area of the planned area meanwhile, agricultural land is still less than the planned area.